2022
DOI: 10.3390/antiox11020228
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat-Diet-Induced Oxidative Stress in Giant Freshwater Prawn (Macrobrachium rosenbergii) via NF-κB/NO Signal Pathway and the Amelioration of Vitamin E

Abstract: Lipids work as essential energy sources for organisms. However, prawns fed on high-fat diets suffer from oxidative stress, whose potential mechanisms are poorly understood. The present study aimed to explore the regulation mechanism of oxidative stress induced by high fat and the amelioration by vitamin E (VE) of oxidative stress. Macrobrachium rosenbergii were fed with two dietary fat levels (LF 9% and HF 13%) and two VE levels (200 mg/kg and 600 mg/kg) for 8 weeks. The results showed that the HF diet decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Oxidative stress refers to the excess reactive oxygen species (ROS) production that can be stimulated by environmental and nutritional factors [ 28 ]. ROS can induce the oxidative damage of biomacromolecules and cellular membrane systems [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress refers to the excess reactive oxygen species (ROS) production that can be stimulated by environmental and nutritional factors [ 28 ]. ROS can induce the oxidative damage of biomacromolecules and cellular membrane systems [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the other key node factor, Relish , correlation analysis data found that Relish was positively correlated with key lipolytic genes Atgl and Cpt1 . Although few studies have shown that Relish enhances lipolysis, one study found that Relish was inhibited when the body fat increased in shrimp [ 35 ]. In addition, Relish was positively correlated with Ulk1 , Beclin1 , and Lc3 , and negatively correlated with p62 .…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ software (National Institutes of Health, Bethesda, MD, USA) adapted from the ORO-staining section algorithm was used to analyze the lipid content of the ORO-staining section and expressed it as the % of the area of lipid-positive hepatopancreas tissue and finally determined its gray value. According to published methods, Hematoxylin-eosin (H&E) and transmission electron microscopy staining for hepatopancreas were conducted [ 32 , 35 ]. To calculate the relative area of the liver vesicles in the H&E stainings, 3 fields were analyzed randomly.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction parameters of RTqPCR are as follows: pre-run at 95°C for 15 min, followed by 40 cycles of denaturation at 95°C for 15 s, and a 60°C annealing step for 34 s. The reaction mixture comprised 2 µl of cDNA, 0.4 µl of forward primer, 0.4 µl of reverse primer, 10 µl of SYBR Premix ExTaqTM (TaKaRa, Dalian, Liaoning, China), 0.4 µl of ROX Reference Dye (TaKaRa, Dalian, Liaoning, China), and 6.8 µl of double-distilled water. β-Actin gene was selected as a reference gene ( 19 ), and each sample was tested in triplicate. Primers were designed online (NCBI, Bethesda, MA, USA) ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%